Desenvolvimento e validação de método analítico por cromatografia líquida para determinação do teor, impurezas orgânicas e produtos de degradação do insumo farmacêutico ativo hemifumarato de quetiapina - Simão, Crislaine (2024)
Quetiapine hemifumarate is an antipsychotic used for the treatment of schizophrenia and bipolar disorder. As required by the regulatory agency, it is necessary to guarantee the quality of the API that will be used for the production of the medicine. A selective and sensitive ultra-performance liquid chromatography method was developed for the quantitative determination of organic impurities, degradation products and quetiapine hemifumarate in the active pharmaceutical ingredient. Efficient chromatographic separation was performed using a Waters Acquity UPLC CSH Phenyl-Hexyl reverse phase column with a length of 100 mm, 2.1 mm in diameter and 1.7 µm particle size as a stationary phase. The mobile phase consisting of a mixture of ammonium acetate buffer pH 9.0 and acetonitrile, in gradient mode, with flow rate of 0.5 mL.min-1, injection volume of 3 µL, temperature of 50 °C and ultraviolet detection at 240 nm. All chromatographic parameters attended, with a resolution greater than 1.5 between quetiapine hemifumarate, organic impurities and degradation products. Quetiapine hemifumarate was also subjected to different stress conditions, in the forced degradation study, where it was proven that the analytical method is indicative of stability, in addition to observing a high susceptibility of the active to oxidation degradation. The method was validated according to ANVISA guidelines, evaluating selectivity, quantification limits, linearity, accuracy, precision and robustness, both for the active and for organic impurities.